The Role of The School Principal In Improving Teacher Performance During The New Adaptation Period at SMPN 1 Perbaungan - Wastuti, Sri Ngayomi Yudha; Pratiwi, Sri Nurabdiah; Jamila, Jamila (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research aims to analyze the role of school principals in improving teacher performance during the adaptation period to new habits. This research uses a descriptive qualitative approach, collecting data from the field, then compiling, analyzing and interpreting, through observation, interviews and documentation studies. The results of this research show that first, school principals have a big role in improving teacher performance during the period of adaptation to new habits. Second, school principals use various effective methods in improving the quality of education. Third, teachers take an active part in implementing the school work program. Thus, the principal as a leader has a big role in the professionalism of the teachers in the school environment he leads. This has an impact on improving the quality of education at SMP Negeri 1 Perbaungan, so that it can help the school graduate students with competencies that are able to compete.